2005
DOI: 10.1080/09537100400028776
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory potency of clopidogrel on ADP-induced platelet activation is not attenuated when it is co-administered with atorvastatin (20 mg/day) for 5 weeks in patients with acute coronary syndromes

Abstract: The antiplatelet potency of clopidogrel may be attenuated by short-term co-administration of lipophilic statins metabolized through the cytochrome P-450, isoform 3A4. We investigated whether the co-administration of atorvastatin (20?mg/day) for 5 weeks, in patients with acute coronary syndromes (ACS) could affect the antiplatelet activity of clopidogrel. Fifty-one patients with the first episode of an ACS were included in the study. All patients underwent percutaneous coronary intervention (PCI) and received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
2
11
2
Order By: Relevance
“…Some studies suggested that lipophilic statins (atorvastatin, lovastatin, and simvastatin) may competitively inhibit CYP3A4 and decrease the generation of clopidogrel's active metabolite, reducing the antiplatelet effect of clopidogrel (7,39,40). On the contrary, other reports were not able to confirm this findings (41)(42)(43)(44)(45)(46). Similarly, we did not observe any drug-drug interaction between clopidogrel and lipophilic statins as measured with both assays in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…Some studies suggested that lipophilic statins (atorvastatin, lovastatin, and simvastatin) may competitively inhibit CYP3A4 and decrease the generation of clopidogrel's active metabolite, reducing the antiplatelet effect of clopidogrel (7,39,40). On the contrary, other reports were not able to confirm this findings (41)(42)(43)(44)(45)(46). Similarly, we did not observe any drug-drug interaction between clopidogrel and lipophilic statins as measured with both assays in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…The objective of this was an assessment of higher doses of atorvastatin on clopidogrel's platelet inhibition [54]. Clopidogrel was given as a 375-mg loading dose followed by 75 mg/day for at least 3 months and platelet function was assessed at baseline and at 5 weeks by using several measures including ADPstimulated aggregation, P-selectin (CD62P) expression, and CD40L expression.…”
Section: Clopidogrel and Hmg-coa Reducatase Inhibitors Interactionmentioning
confidence: 99%
“…Clopidogrel is mainly metabolized into its active metabolite via cytochrome P-450 3A4; however, upregulation of cytochrome P-450 2B6, 2C19 could compensate for decreased activity of cytochrome P-450 3A4 during clopidogrel and atorvastatin co-administation, even in the early stage. 5,23 Although the lipid profiles were more favorable in the ATOR40 Group regarding the LDL-C and TC concentrations, no significant differences were found in reducing late lumen loss and inflammatory markers, such as IL-6, TNF-α, sICAM-1, sVCAM-1 and hs-CRP, compared with the ATOR10 Group. This might be because other medications, such as angiotensin-converting enzyme inhibitors and angiotensin-receptor blockers, were administered during the study.…”
Section: Discussionmentioning
confidence: 86%
“…20 However, others have suggested that atorvastatin does not influence the antiplatelet effect of clopidogrel. 3,5,21 Many clinicians were confused by these controversial results and questioned the safety of clopidogrel and atorvastatin co-administration in "real world" clinical practice. Large clinical trials have answered this question about safety; for example, the Clopidogrel for Reduction of Events During Observation (CREDO) trial demonstrated that there was no adverse effect on the 1-year clinical outcomes with clopidogrel and lipophilic statin co-administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation